2003
DOI: 10.1063/1.1606528
|View full text |Cite
|
Sign up to set email alerts
|

Baffled probe for real-time measurement of space potential in magnetized plasma

Abstract: A probe for measurements of space potential in magnetized plasma is tested in a fully ionized, barium, Q-machine plasma. The probe consists of a tungsten wire tip, situated perpendicular to the magnetic field, that is partially shielded by ceramic baffles (masks). The probe works under the condition that the electron Larmor radius is much smaller than the probe radius, and that the ion Larmor radius is comparable to or larger than the probe radius. By rotating the baffle configuration around the probe tip, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…In this case it can be shown that in a Maxwellian plasma the floating potential of such a probe becomes equal to the plasma potential. One type of such a probe is the ball-pen probe [13,14], another one the plug probe [15] and the baffled probe [16].…”
Section: Introductionmentioning
confidence: 99%
“…In this case it can be shown that in a Maxwellian plasma the floating potential of such a probe becomes equal to the plasma potential. One type of such a probe is the ball-pen probe [13,14], another one the plug probe [15] and the baffled probe [16].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown [13,14] that a baffled probe is a convenient and simple non-emitting instrument for the real-time monitoring of dc and ac values of both space potential and electron temperature in magnetized plasma. The probe works under the condition that electron Larmor radius is much smaller than the probe radius, and the ion Larmor radius is comparable to or larger than the probe radius.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the plug probe must be aligned precisely with respect to the magnetic field and this is difficult to maintain. This paper evaluates the ability of the so-called baffled probe [16] to distinguish space-potential and electron/iontemperature oscillations. The baffled probe, like the plug probe, is an ion-sensitive probe, but is constructed to have a wider range of orientation angles.…”
Section: Introductionmentioning
confidence: 99%